Implementing Cisco HyperFlex Solutions - Patel, Jalpa; Velasco, Manuel; Shukla, Avinash (Cisco Press, 2020)
Cisco HyperFlexsolutions enhance data center efficiency, agility, and resiliency by tightlyintegrating core infrastructure (compute, storage, networking, and system management), increasing automation, and simplifying lifecycle management. Thisauthoritative, comprehensive guide brings together knowledge, detailed configurationoptions, and real-world case studies for successfully deploying Cisco HyperFlextechnologies in environments of all types. Three expert authorspresent easy-to-understand overviews of key Hyperconverged Infrastructure (HCI)concepts, show how HyperFlex technologies apply them, and present detailedreference examples with topologies, configurations, and verifications for eachmajor feature. Drawing on extensive experience helping Cisco customers adoptHyperFlex, they present best practices for optimizing design, streamliningdeployment, avoiding pitfalls, and maximizing value. This guide will be indispensable to everyIT and network professional, manager, or consultant involved in planning, deploying, or operating Cisco HyperFlex or evaluating any HCI solution. Reflecting current trends in HCI deployment, it will be valuable in bothsmall-scale environments and large-scale data centers. Explore how and why data centers have evolved from traditional to convergedand hyperconverged infrastructure Review the essentials of HyperFlex hyperconverged infrastructure connectivity Understand HyperFlex Data Platform architecture, components, topologies, and supported hardware Compare HyperFlex standard, stretch, and edge clusters, and understand theirrespective roles Install and deploy each type of Cisco HyperFlex cluster, includingpreparation, prerequisites, and components Manage HyperFlex via HyperFlex Connect: HX storage cluster status, components, encryption, replication, and more Maintain HyperFlex: clustering, virtual machine management, native snapshots, ReadyClones, and more Scale HyperFlex clusters, replace hardware, and upgrade software Configure and manage advanced HyperFlex Data Platform disaster recoveryfeatures Integrate supported third-party data protection solutions, includingVeeam Availability Suite, Cohesity, and Commvault Utilize the cloud-based Cisco Intersight platform to deploy HyperFlexAnywhere, including edge and standard clusters.